2020
DOI: 10.2147/orr.s170964
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sternoclavicular Joint Instability: Symptoms, Diagnosis And Management</p>

Abstract: Sternoclavicular joint (SCJ) instability is a rare condition and results from either a traumatic high energy impact, such as a motor vehicle crash or contact sports injury, or nontraumatically as a result of structural pathology. The infrequency of this injury has contributed to its diagnosis being missed as well as the paucity of literature on treatment and outcomes. Patients with SCJ instability often report diminished range of motion as well as shoulder girdle pain. The presentation of instability in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 67 publications
0
26
0
2
Order By: Relevance
“…The sternoclavicular joint is the only synovial joint connecting shoulder girdle to the upper trunk [ 1 ]. The special shape of the medial clavicle (concave from front to back and convex from top to bottom) gives the sternoclavicular joint its saddle shape and provides the joint with ability to move in three planes (elevation/depression, protraction/retraction, rotation) [ 2 ] ( Fig. 5 ).…”
Section: Clinical Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sternoclavicular joint is the only synovial joint connecting shoulder girdle to the upper trunk [ 1 ]. The special shape of the medial clavicle (concave from front to back and convex from top to bottom) gives the sternoclavicular joint its saddle shape and provides the joint with ability to move in three planes (elevation/depression, protraction/retraction, rotation) [ 2 ] ( Fig. 5 ).…”
Section: Clinical Discussionmentioning
confidence: 99%
“…The study of Spencer et al demonstrated that the joint capsule stabilizes the joint against anterior/posterior subluxation [ 10 ]. Meanwhile, the costoclavicular ligament and intraarticular disc prevents the medial clavicle from upward and medial displacement respectively [ 2 ].
Fig.
…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows for the guided lifting, lowering, and forward and backward movement of the shoulder, as well as its circumduction. Injuries of the SCJ are rare [ 1 ] and can be easily missed in the primary survey of a patient, especially in those who are polytraumatized [ 2 , 3 ]. SCJ injuries are clinically categorized into three stages: sprain, subluxation, and dislocation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior dislocations or subluxations of the SCJ are more common than posterior dislocations and can result in functional impairment [ 6 ]. In the case of anterior subluxations and dislocations, the treatment may include reduction and rehabilitation, though some instances may require stabilization through surgical intervention and management [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%